LEMBAGA DEPONERING SEBAGAI IMPLEMENTASI ASAS OPORTUNITAS PERKARA PIDANA DI INDONESIA - Gema Yudha (LPPM Universitas Ekasakti Padang, 2020)
Deponering or exclusion of a criminal case for the sake of interest is the authority of the Attorney General of the Republic of Indonesia in accordance with the provisions contained in Article 35 sub c of Law No. 16 of 2004 concerning the Basic Provisions of the Attorney General's Office of the Republic of Indonesia, as well as their explanations. Leaving aside the case as referred to in this provision is the implementation of the principle of opportunity in which a case (criminal act) when it is submitted to a trial is expected to cause a shock in the community or by trial the case will have a negative effect on the wider community, as happened in the case of Bibit Samad Rianto and Chandra M. Hamzah that occurred in 2009 until 2011. The problem studied was about the position of deponering institutions as the implementation of the principle of opportunity by the Attorney General and what were the reasons for the Attorney General to decide on deponering of Bibit Samad Rianto and Chandra M. Hamzah cases? This research is supported by primary data secondary data in the form of interviews with the parties in the Center for Research and Development of the Attorney General's Law. From the results of research and analysis obtained that the existence of deponering institutions as the implementation of the principle of opportunity by the Attorney General is a prosecution must be done if formal requirements have been met and must also be deemed necessary in the public interest, so that the prosecutor will not demand a case before the elements of public interest has been fulfilled. And the reason the Attorney General decided to deponering the Bibit Samad Rianto and Chandra M. Hamzah case was based on the consideration that if the case in the name of the suspects Bibit Samad Rianto and Chandra M. Hamzah was transferred to the court, it would have the effect of disturbing the performance of the Corruption Eradication Commission (KPK). as well as managerial in carrying out their duties and authorities, so as to prejudice the public interest, namely the interests of the nation, state or society and also in order to protect efforts to eradicate corruption as a whole.